2020
DOI: 10.1007/s00449-020-02347-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of Aspergillus niger strains for endogenous pectin-depolymerization capacity and suitability for d-galacturonic acid production

Abstract: Pectinaceous agricultural residues rich in d-galacturonic acid (d-GalA), such as sugar beet pulp, are considered as promising feedstocks for waste-to-value conversions. Aspergillus niger is known for its strong pectinolytic activity. However, while specialized strains for production of citric acid or proteins are well characterized, this is not the case for the production of pectinases. We, therefore, systematically compared the pectinolytic capabilities of six A. niger strains (ATCC 1015, ATCC 11414, NRRL 312… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 55 publications
(78 reference statements)
0
17
0
Order By: Relevance
“…This analysis also included a comparison between N400 and N402. The results indicated that the growth profile in bioreactor was similar, although the N402 strain reached a higher maximum dry biomass level compared to N400 (2.28 ± 0.12 g/L for N400 vs 3.38 ± 0.07 g/L for N402) (Schäfer et al, 2020). The morphology of the mycelium of the N400 and N402 strains during cultivation on pectin was also examined and compared.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This analysis also included a comparison between N400 and N402. The results indicated that the growth profile in bioreactor was similar, although the N402 strain reached a higher maximum dry biomass level compared to N400 (2.28 ± 0.12 g/L for N400 vs 3.38 ± 0.07 g/L for N402) (Schäfer et al, 2020). The morphology of the mycelium of the N400 and N402 strains during cultivation on pectin was also examined and compared.…”
Section: Discussionmentioning
confidence: 97%
“…An important consideration is to which extent the mutations in the kinesin-like protein and the transcription factor that lead to shorter conidiophore stalk and reduced radial growth identified in this study might affect the conclusions reached in previous studies. Schäfer et al (2020) performed a comparative study in which different A. niger strains were compared for growth under controlled conditions. This analysis also included a comparison between N400 and N402.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No growth, no sorbitol consumption, no D-GalA consumption, and no L-GalOA production were observed with S. cerevisiae SiHY001 (data not shown). Enzymatic hydrolysis of SBPP had been performed in 100 mM sodium acetate buffer (Schäfer et al 2020). As acetic acid is known to affect the metabolism of S. cerevisiae already at concentrations as low as 3 mM (Sousa et al 2012), growth of S. cerevisiae SiHY001 was studied in miniaturized single-use stirred tank reactors with diverse buffers and buffer concentrations at pH 5.0 in SC medium (sodium acetate, sodium citrate, potassium acetate, and potassium citrate).…”
Section: Growth Of S Cerevisiae Sihy001 With Varying Buffer Componentsmentioning
confidence: 99%